Revisiting the role of cancer-associated fibroblasts in tumor microenvironment - Lan, Xiaolei; Li, Wenyang; Zhao, Kai; Wang, Jianpeng; Li, Shifang; Zhao, Hai (Frontiers in Immunology, 2025)
Cancer-associated fibroblasts (CAFs) are integral components of the tumor microenvironment playing key roles in tumor progression, metastasis, and therapeutic resistance. However, challenges persist in understanding their heterogeneity, origin, and functional diversity. One major obstacle is the lack of standardized naming conventions for CAF subpopulations, with current systems failing to capture their full complexity. Additionally, the identification of CAFs is hindered by the absence of specific biomarkers, limiting the precision of diagnostic and therapeutic strategies. In vitro culture conditions often fail to maintain the in vivo characteristics of CAFs, which complicates their study and the translation of findings to clinical practice. Although current detection methods, such as antibodies, mRNA probes, and single-cell transcriptomics, offer insights into CAF biology, they lack standardization and fail to provide reliable quantitative measures. Furthermore, the dynamic interactions between CAFs, tumor cells, and immune cells within the TME remain insufficiently understood, and the role of CAFs in immune evasion and therapy resistance is an area of ongoing research. Understanding how CAFs influence drug resistance and the immune response is essential for developing more effective cancer therapies. This review aims to provide an in-depth analysis of the challenges in CAF research, propose future research directions, and emphasize the need for improved CAF-targeted therapeutic strategies. By addressing these gaps, it seeks to highlight the potential of CAFs as targets for overcoming therapeutic resistance and enhancing the efficacy of cancer treatments.